2020
DOI: 10.1111/cas.14630
|View full text |Cite
|
Sign up to set email alerts
|

Short somatic alterations at the site of copy number variation in breast cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We found that a large number of copy number alterations were detected, with amplification of part of chromosomes 1q, 8q, 16p, and 17q, and deletion of part of chromosomes 8p, 16q, and 17p ( Figure 1A ). Copy number variation chromosome maps also validated the copy number variation profile of these regions ( 26 , 27 )( Figure 1B ). At the same time, we found that some chromosomes showed the same variation trend on the entire chromosome, such as the overall copy number amplification of chromosome 3, the overall copy number loss of chromosome 4, but other chromosomes such as chromosomes 1, 8 and 16 showed the opposite trend of copy number variation at arm-level ( Figure 1B ).…”
Section: Resultssupporting
confidence: 54%
“…We found that a large number of copy number alterations were detected, with amplification of part of chromosomes 1q, 8q, 16p, and 17q, and deletion of part of chromosomes 8p, 16q, and 17p ( Figure 1A ). Copy number variation chromosome maps also validated the copy number variation profile of these regions ( 26 , 27 )( Figure 1B ). At the same time, we found that some chromosomes showed the same variation trend on the entire chromosome, such as the overall copy number amplification of chromosome 3, the overall copy number loss of chromosome 4, but other chromosomes such as chromosomes 1, 8 and 16 showed the opposite trend of copy number variation at arm-level ( Figure 1B ).…”
Section: Resultssupporting
confidence: 54%
“…Immunostaining for Ki‐67 was performed. The immunostaining method followed our previous report 31 . The average Ki‐67 positivity (%) was calculated from the number of Ki‐67 positive and Ki‐67 negative cells counted using BZ‐X800 Analyzer software (Keyence) from six independent rectangular regions (400× field of view) of each xenograft tumor.…”
Section: Methodsmentioning
confidence: 99%
“…The immunostaining method followed our previous report. 31 The average Ki‐67 positivity (%) was calculated from the number of Ki‐67 positive and Ki‐67 negative cells counted using BZ‐X800 Analyzer software (Keyence) from six independent rectangular regions (400× field of view) of each xenograft tumor. Figure S2 shows Ki‐67 staining images of H1650 (cell line with the highest Ki‐67 positivity in the BE phenotype), HCC4006 (cell line with the lowest Ki‐67 positivity in the BE phenotype), H460 (cell line with the highest Ki‐67 positivity in the non‐BE phenotype), and H1651 (cell line with the lowest Ki‐67 positivity in the BE phenotype).…”
Section: Methodsmentioning
confidence: 99%
“…The APOBEC3B gene, which is located on Chromosome 22q13.1, regulates breast cancer cell development by promoting ER transcriptional activity (Cescon et al 2015). APOBEC3B copy number gain is associated with poor survival in patients with ER + breast cancer (Periyasamy et al 2015;Murakami et al 2021). A summary of each detected event along with the CNV state (1 = two copy losses, 2 = one copy loss, 3 = neutral, 4 = one copy gain, 5 = two copy gains, 6 = three or more copy gains) is given in Supplemental Tables S8 and S9, with source data identities.…”
Section: Expression-based Cnv Inferencementioning
confidence: 99%